Prosedur Pengurusan Clearance Out Kapal Berbenderaasing pada Kantor KSOP oleh PT Tirta Permai Bahari Cabang Pontianak: Penelitian - Lufthi Aulia Rahman; Meriah Kita Deliani (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to provide an in-depth analysis of the clearance out procedures for foreign-flagged vessels carried out by PT Tirta Permai Bahari, Pontianak Branch, as the appointed shipping agent at Kijing Tanjung Pura Port. The clearance out process includes the preparation and submission of all departure documents as well as coordination with relevant authorities, such as the Harbourmaster’s Office (KSOP), Customs, Port Health Quarantine Office, Immigration, and Pelindo. As the representative of the shipowner, the shipping agent plays a crucial role in ensuring the smooth administration of a vessel’s departure in accordance with applicable regulations. Effective collaboration and communication between the agent and the relevant authorities significantly influence the efficiency of the clearance out process. The accuracy and timeliness of document processing depend on the completeness of the required documents and the readiness of all parties involved. In preparing this paper, the authors employed two research methods: field research, conducted through direct observation of operational activities on site, and library research, involving an examination of literature, regulations, and relevant electronic sources (e-books) to strengthen the theoretical foundation and discussion.